2008
DOI: 10.1111/j.1530-2415.2008.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Patriotism Measures to Critical Thinking and Emphasis on Civil Liberties versus National Security

Abstract: Students in a large undergraduate course (N = 236) at a major state university in the Southeastern United States took a standardized critical thinking test and four short sociopolitical scales (constructive patriotism, blind patriotism, respect for civil liberties, and emphasis on national security) at the beginning of the fall semester 2007. Although numerous published studies have addressed relationships between types of patriotism and various sociopolitical variables, these studies typically have not target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…One focal difference between blind and constructive patriots is how the boundaries between groups are perceived. Blind patriotism emphasizes group boundaries (Staub, 1997), and has been shown to be associated with perceived intergroup threat and feelings of vulnerability (Spry & Hornsey, 2007;Schatz et al, 1999;Williams, Foster & Krohn, 2008). For example, Spry and Hornsey (2007) showed that the perception of an intergroup threat mediates the association between blind patriotism and general support for immigration.…”
Section: Blind and Constructive Patriotism And Group Boundariesmentioning
confidence: 99%
“…One focal difference between blind and constructive patriots is how the boundaries between groups are perceived. Blind patriotism emphasizes group boundaries (Staub, 1997), and has been shown to be associated with perceived intergroup threat and feelings of vulnerability (Spry & Hornsey, 2007;Schatz et al, 1999;Williams, Foster & Krohn, 2008). For example, Spry and Hornsey (2007) showed that the perception of an intergroup threat mediates the association between blind patriotism and general support for immigration.…”
Section: Blind and Constructive Patriotism And Group Boundariesmentioning
confidence: 99%
“…However they are considered as conceptually and empirically distinct based on attitudes towards out-groups. Whilst nationalism incorporates a desire for superiority, domination over other countries and fanaticism (Federico et al 2005), patriotism refers to a more critical form of attachment and a more open view of other nations (Williams et al 2008). The third dimension, internationalism, describes a wider concern for the well-being of the global population that transcends national borders, an admiration for the qualities of other nations and a willingness to co-operate to address global problems (Tsai et al 2013).…”
Section: National Identitymentioning
confidence: 99%
“…Also, nationalism and patriotism are positively correlated with more hawkish foreign-policy attitudes and increased support for military action (Federico et al, 2005). In contrast, nationalism and patriotism are negatively related to critical thinking skills (Williams, Foster, & Krohn, 2008), along with reduced political knowledge and student grade point average (GPA) scores (Schatz, Staub, & Lavine, 1999). Critical thinking skills, knowledge, and learning performance are all key factors in the context of training technologies.…”
Section: Social Identitymentioning
confidence: 99%